Biomimetic Design of 3D Fibrous Mesh Reinforced Hydrogel Replicating the Form and Function of the Intervertebral Disc. Issue 4 (4th April 2023) - Lu, Changbo; Huang, Xinyi; Yan, Hao; Wang, Ya; Wang, Yibo; Zhuo, Shuyun; Wei, Congying; Qiu, Haiyang; Yang, Xiaojiang; Zhang, Yang; Liu, Mingjie; Lei, Wei
Abstract : A Biomimetic Design of the Artificial Intervertebral Disc In article number 2200254 Wei Lei, Mingjie Liu, Yang Zhang, and co‐workers fabricate biomimetic prototype of artificial intervertebral disc with nature‐mimicking mechanics and structure. The design possesses an angle‐ply fiber scaffold with multi‐scale structural hierarchy, which exhibits osmotic behaviors, non‐linear viscoelasticity and durability, enduring it with a great potential for total cervical disc replacement in future.